Permasalahan-permasalahan yang Menyertai Erupsi Gigi - Indri Kurniasih (Universitas Muhammadiyah Yogyakarta, 2008)
Tooth eruption process is an normal physiological process. It may become abnormal there disturbances intervered within the process. Several disturbances such as trauma, hereditary factors, and pathological disorders can cause some problems which may leads to dental disorders if it were remain untreated. These matters have to become a serious concern of the dentists. There are several problems which are frequently associated with tooth eruption process such as ankylosis, eruption cyst, eruption hematoma and ectopic eruption. Each of these problems has their own specific clinical characteristic .Moreover, some of the problems needs special treatments to assure that dental anomaly resulted will not develop further and dental eruption is not disturbed. The aim of the writing is to elaborate the etiology, sign and clinical symptoms, and also treatment of problems during tooth eruption.Proses erupsi gigi merupakan suatu proses fisiologis yang normal. Bisa menjadi tidak normal ketika terjadi gangguan pada proses tersebut. Beberapa gangguan berupa trauma, faktor herediter, kondisi patologis terkadang menimbulkan permasalahan yang jika dibiarkan akan berlanjut menimbulkan kelainan pada gigi. Hal ini perlu menjadi perhatian serius oleh dokter gigi. Ada beberapa permasalahan yang sering menyertai proses erupsi gigi diantaranya ankylosis, eruption cyst, eruption hematoma dan ectopic eruption. Permasalahan-permasalahan tersebut mempunyai karakteristik yang khas. Beberapa diantaranya bahkan memerlukan penanganan khusus agar kelainan gigi tidak berlanjut dan proses erupsi gigi tidak terganggu. Penulisan ini bertujuan untuk menguraikan tentang etiologi, tanda dan gejala klinis serta perawatan dari permasalahan-permasalahan yang timbul selama proses erupsi gigi.